INTERFERENSI BAHASA INDONESIA PADA VIDEO TIKTOK @NADIATILEM “REAL TALK: KENAPA KOREA SELATAN LEBIH MAJU DARIPADA INDONESIA?” - Imania, Cahya Savitri; Kirani, Eka Dewi; Farah Mutia, Sabrina; Autar, Nayla (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2024)
Abstract The purpose of this study is to describe Indonesian language interference in @Nadiatilem's Tiktok video which discusses "Real Talk: Why is South Korea More Advanced Than Indonesia?". This research aims to explain the forms of Indonesian language interference into Betawi and English spoken by Nadia in this Tiktok video. To determine the interference in this article, the author uses a qualitative descriptive method and the source is the Tiktok @Nadiatilem video. The technique used to generate data is the listening technique. The main data is Nadia Tilem's speech. The theory used in this study is Abdul Chaer's theory (1995) which states that if a language changes in connection with the contact of that language with other language elements that occur in bilingual speakers. The conclusion of this research is that interference often occurs because of the lack of mastery of one language or the utterance is sounded with an element of accident. Keywords: Interference, language, Tiktok.